Information and Communication Technologies for Jobs in the Pacific - Beschorner, Natasha (World Bank, Washington, DC, 2015)
The Pacific region is in the midst of an information and communications technology (ICT) revolution in which small island countries are increasingly connected to the global economy. The regions improving internet connectivity presents an opportunity for Pacific Island countries (PICs) to overcome their inherent limitations, and help address the long-standing issues of employment and income generation, which is vital to accelerate progress towards ending poverty and creating an inclusive society. The PICs possess unique vulnerabilities that make addressing poverty and development challenges particularly difficult and complex. The purpose of this study is to examine the feasibility of leveraging ICT to help generate job opportunities in the PICs. This is because of the positive experiences that several countries, including small island economies, have had in generating new types of employment opportunities. The study’s main focus is on cities and urban areas, given the still low availability of internet infrastructure and services in rural and remote areas and islands in the Pacific region. The study focuses specifically on the information technology (IT) - enabled global outsourcing services (GOS) industry. ICT covers diverse subsectors that include telecommunications and IT hardware and software.